Temporal and Spectral Analysis of the Unique and Second-brightest Gamma-Ray Burst GRB 230307A: Insights from GECAM and Fermi/GBM Observations - R. Moradi; C. W. Wang; B. Zhang; Y. Wang; S.-L. Xiong; S.-X. Yi; W.-J. Tan; M. Karlica; S.-N. Zhang (The Astrophysical Journal)
In this study, we present the pulse profile of the unique and the second-brightest gamma-ray burst GRB 230307A, and analyze its temporal behavior using a joint GECAM–Fermi Gamma-ray Burst Monitor (GBM) time-resolved spectral analysis. The utilization of GECAM data is advantageous as it successfully captured significant data during the pileup period of the Fermi/GBM. We investigate the evolution of its flux, photon fluence, photon flux, peak energy, and the corresponding hardness–intensity and hardness–flux correlations. The findings within the first 27 s exhibit consistent patterns reported previously, providing valuable insights for comparing observations with predictions from the synchrotron radiation model invoking an expanding shell. Beyond the initial 27 s, we observe a notable transition in the emitted radiation, attributed to high-latitude emission, influenced by the geometric properties of the shells and the relativistic Doppler effects. By modeling the data within the framework of the large-radius internal shock model, we discuss the required parameters as well as the limitations of the model. We conclude that a more complicated synchrotron emission model is needed to fully describe the observational data of GRB 230307A.